Effect of additives on the structure and performance of polysulfone hollow fiber membranes for CO2 absorption - Mansourizadeh, A. (Elsevier, 2010)
Porous polysulfone (PSf) hollow fiber membranes were fabricated via a phase-inversion method by using low molecular weight additives in the spinning dopes. Polyethylene glycol (PEG200), ethanol, glycerol and acetic acid were used as the additives. An aqueous 95 wt.% 1-methyl-2-pyrrolidone (NMP) solution was used as neutral bore fluid to fabricate inner skinless hollow fibers membranes. The precipitation rate of the polymer dopes with the different additives was studied using cloud point measurement. Effect of the additives on the resulting membrane structure, surface porosity, pore size, critical water entry pressure (CEPw) and CO2 absorption performance were investigated. Cloud point diagrams indicated that the precipitation rate of the polymer dopes increased following the trend of glycerol > acetic acid > PEG200 > ethanol. Results of gas permeation tests showed that glycerol and PEG200 as additives provided the membranes with the largest and smallest pore size, respectively. Moreover, all the additives resulted in an increase in the surface porosity. The cross-section and inner surface of the membranes were examined via a field emission scanning electronic microscopy (FESEM). Glycerol in the spinning dope provided the membrane structure with a thin finger-like and a thick sponge-like layer, which resulted in a higher CEPw and CO2 absorption rate than the other PSf hollow fiber membranes.